Skrining Perilaku Gaya Hidup Mahasiswa sebagai Faktor Risiko Dini Penyakit Jantung dan Diabetes Melitus - Abul A’la Al-Maududi; Hafizh Rafid Hardian; Fayola Nabila Putri; Muhammad Hibban Ataridan Hambal Arifin; Ratu Mulya Hasasita (Lembaga Pengembangan Kinerja Dosen, 2026)
Noncommunicable diseases (NCDs) such as diabetes mellitus (DM) and heart disease are now beginning to manifest at a younger age due to the accumulation of overlooked behavioral risk factors. College students, as a transitional group, are vulnerable to unhealthy lifestyles due to academic pressures and financial constraints. This study aims to screen students’ lifestyle behaviors and identify their association with family medical history as an early risk factor for NCDs. This quantitative study with a cross-sectional design involved 50 students from the Faculty of Public Health at Muhammadiyah University of Jakarta, selected using voluntary response sampling in May–June 2026. Data on lifestyle behaviors (dietary patterns, sleep duration, screen time) and family medical history were collected via a digital questionnaire and analyzed using descriptive statistics. Results showed that 28% of students had irregular eating patterns, 34% were sleep-deprived (<6 hours/night), and 42% had high screen time intensity. A total of 18% of respondents had a family history of diabetes mellitus (DM) and 38% had a family history of heart disease. The combination of a sedentary lifestyle, irregular eating patterns, and sleep restriction significantly increases the risk of insulin resistance and cardiovascular burden, particularly in subjects with a genetic predisposition. In conclusion, there is a high prevalence of NCD-related risk behaviors among college students, exacerbated by economic factors and digital dependency. The interaction between modifiable lifestyle factors and genetic susceptibility calls for proactive screening programs and context-specific health education on college campuses as fundamental preventive measures to break the chain of chronic disease risk early on.